Assistance for the Kendal Sharia Economic Community Regional Management in Preparing a Halal Tourism Area - M Fatchurrohman; Agus Triyani; Nugroho Eko Budiyanto; Siti Luluk Mawanti; Muhammad Fahmi Yusuf; Muhammad Ashlyzan B Razik (Jurnal Pemberdayaan Masyarakat, 2025)
The development of halal tourism is a strategic effort to enhance regional competitiveness and achieve Indonesia’s vision of becoming a global halal hub. This community service project was conducted at Wisata Halal Jabal Nur, South Kaliwungu, Kendal, focusing on empowering Micro, Small, and Medium Enterprises (MSMEs) to obtain halal certification and enhance digital-based promotion. The program provided training, technical assistance, and mentoring to help MSMEs comply with halal standards and enhance their business management. The methods included socialization, Focus Group Discussions (FGD), digital financial recording workshops, halal certification facilitation, and the development of official websites and social media platforms for tourism promotion. Collaboration among lecturers, students, MSMEs, tourism managers, and local governments has built a sustainable ecosystem for the growth of halal tourism. The results show that halal certification increases MSME awareness of halal integrity, while digital promotion effectively expands market reach and reinforces Jabal Nur’s image as a religious and inclusive tourism destination. This integrative model enhances consumer trust and strengthens the local economy. Moreover, the study contributes to global science by presenting an evidence-based framework that links digital transformation, community empowerment, and Islamic economic principles, providing new insights for scholars and policymakers in advancing sustainable and globally competitive halal tourism development.